Non-invasive ventilation effectiveness and the effect of ventilatory mode on survival in ALS patients. Issue 1 (March 2014) - Sancho, Jesus; Servera, Emilio; Morelot-Panzini, Capucine; Salachas, François; Similowski, Thomas; Gonzalez-Bermejo, Jesus
Abstract Non-invasive ventilation (NIV) prolongs survival in amyotrophic lateral sclerosis (ALS), but there are no data with which to compare the effectiveness of the different ventilator modes – volume (Vol-NIV) or pressure-cycled (Pres-NIV) ventilation – in ALS. We aimed to determine whether the ventilatory mode has an effect on ventilation effectiveness and survival of ALS patients using NIV. We used a retrospective study that included all ALS patients for whom NIV was indicated in two referral units: one using Vol-NIV and the other using Pres-NIV. Demographic, functional and nocturnal gas exchange parameters at NIV initiation were recorded. Eighty-two ALS patients ventilated using Pres-NIV and 62 using Vol-NIV were included. No differences were found in survival from NIV initiation between Vol-NIV (median 15.00 (7.48–22.41) months) and Pres-NIV (median 15.00 (10.25–19.75) months, p = 0.533) patients. Effective NIV was achieved in 72.41% Vol-NIV patients and in 48.78% Pres-NIV patients (p < 0.001). Ventilator mode (OR 12.066 (4.251–32.270), p < 0.001) and severity of bulbar dysfunction (OR 1.07 (1.011–1.133), p = 0.02) were the variables correlated with effective NIV. In conclusion, although Vol-NIV provides more effective ventilation, Vol-NIV and Pres-NIV present similar survival in ALS. Effectiveness of NIV is related to the severity of bulbar dysfunction.